Large eddy simulation of dam‐break‐driven swash on a rough‐planar beach. Issue 2 (17th February 2017) - Kim, Yeulwoo; Zhou, Zheyu; Hsu, Tian‐Jian; Puleo, Jack A.
Abstract: Turbulence characteristics in the swash zone are investigated using a 3‐D large eddy simulation model. The numerical model is implemented based on OpenFOAM which solves the filtered Navier‐Stokes equations for two immiscible fluids with a standard Smagorinsky subgrid‐scale closure. The numerical model is validated with laboratory data for swash flow driven by a dam‐break apparatus. The model results demonstrate that the main characteristics of turbulence in the swash zone are different from those in the surf zone, which are mainly induced by surface wave breaking. During uprush phase, bore‐generated turbulence has 2‐D turbulence characteristics because of limited water depth. Near‐bed‐generated turbulence is mainly observed during backwash. Turbulence production and turbulent dissipation rate estimated from the model results indicate an imbalance, possibly due to advection at swash front and large roughness used. Touching down of turbulent coherent structure (TCS) is observed during uprush, which drives intense bed shear stress. During the backwash, interaction between TCS and bed is less clear. However, finger‐like patterns in the spatial extent of bed shear stress and vertical components of vorticity are predicted during the backwash. The location of the strongest finger patterns in the vertical direction is collocated with that of maximum turbulence production. These finger patterns are likely caused by boundary layer instabilities injected vertically from the bed. Key Points: A comprehensive study of a large‐eddy simulation model for dam‐break‐induced swash flows was conducted Uprush flow is dominated by turbulent coherent structures interacting with the bed Finger patterns observed during backwash are associated with a boundary layer instability